Post‐mastectomy radiation therapy and overall survival after neoadjuvant chemotherapy. Issue 6 (13th January 2017) - Kantor, Olga; Pesce, Catherine; Singh, Puneet; Miller, Megan; Tseng, Jennifer; Wang, Chi‐Hsiung; Winchester, David J.; Yao, Katharine
Abstract : Background: The role of postmastectomy radiation therapy (PMRT) after neoadjuvant chemotherapy (NAC) and mastectomy is unclear, especially in patients that have post‐treatment tumor negative axillary nodes (ypN0). Methods: The National Cancer Data Base was used to identify women that had PMRT after NAC and mastectomy for clinically node positive (cN1‐2) disease from 2004 to 2008. Median follow‐up time was 69 months. Results: 8, 321 patients were included for analysis, and 6140 (65.6%) had cN1 disease and 2181 (23.3%) had cN2 disease. On adjusted survival analysis, PMRT was associated with an overall survival (OS) benefit in both patients with cN1 (5‐yr OS 75.8% vs. 71.9%, P  < 0.01) and cN2 (5‐yr OS 69.2% vs. 58.6%, P  < 0.01) disease. In the subgroup of patients that were ypN0 after NAC, there was no significant survival difference ( P  > 0.11) for PMRT compared to those patients who were not ypN0, except for patients with hormone‐receptor negative tumors, who had improved OS with PMRT (HR 0.65, P  < 0.01). Conclusions: PMRT is associated with improved OS in patients with cN1 and cN2 disease after NAC and mastectomy. However, in the subgroup of patients that were ypN0 after NAC, PMRT improved OS for hormone‐receptor negative patients but not hormone‐receptor positive patients.